Peningkatan Literasi Digital UMKM melalui Pelatihan Pemasaran Digital dan E-Commerce di Kota Cirebon - Ade Rizki Rinaldi; Agus Bahtiar; Aziz Chairul Imam; Bima Anurgraha Djajnegara (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community service program aims to improve digital literacy among Micro, Small, and Medium Enterprises (MSMEs) through training in online marketing and e-commerce. The background of this program stems from the low level of understanding and skills among MSME actors in utilizing digital technology to support business marketing and management online. The problems faced by MSME partners include limited use of social media, suboptimal management of online marketplaces, and a lack of digital branding strategies to expand market reach. To address these issues, the program offers a solution in the form of digital literacy training, which includes online marketing strategies, social media optimization, marketplace account management, and digital-based transaction management. The implementation method of this program involves several stages: identifying partner needs, preparing training materials and modules, conducting workshops, providing intensive mentoring, and evaluating the development of the partners. The results of this program show that participants experienced a significant increase in their understanding and skills in online marketing. Most participants were able to create and manage social media and marketplace accounts for their businesses and apply digital marketing strategies to promote their products. In addition, this program produced several outputs, including training modules, digital guide templates, activity documentation, and the formation of a digital-based MSME community. With this program, it is expected that MSMEs can become more adaptive to technological developments, expand their market reach, increase their revenue, and strengthen their competitiveness in an ever-evolving digital era. The program also recommends ongoing mentoring so that MSMEs can continuously develop their digital skills in a sustainable manner.